2013
DOI: 10.3233/ves-130501
|View full text |Cite
|
Sign up to set email alerts
|

Motion sickness susceptibility in healthy subjects and vestibular patients: Effects of gender, age and trait-anxiety

Abstract: Several studies have suggested that anxiety may play a role in motion sickness susceptibility (MSS) variability. This study aimed to assess motion sickness susceptibility in healthy subjects and chronic vestibular patients and to investigate its relationship to gender, age and trait-anxiety. Healthy subjects (n = 167) and chronic dizzy patients with various vestibulopathies (n = 94), aged from 20 to 92 years old, were asked to complete Motion Sickness Susceptibility questionnaire (MSSQ) and trait-anxiety quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
76
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 14 publications
13
76
2
2
Order By: Relevance
“…Previous research has found inconsistent findings when looking at older samples (Kennedy et al, 2010;Benoit et al, 2015). Even though age has been reported as a user characteristic likely to predict motion sickness (Golding, 2006), the results from this review support previous research that there may be a decline in susceptibility to VR sickness as a person ages (Paillard et al, 2013). However, as there are a limited number of studies including older samples, these results should be interpreted with caution.…”
Section: Age and Vr Sicknesssupporting
confidence: 65%
“…Previous research has found inconsistent findings when looking at older samples (Kennedy et al, 2010;Benoit et al, 2015). Even though age has been reported as a user characteristic likely to predict motion sickness (Golding, 2006), the results from this review support previous research that there may be a decline in susceptibility to VR sickness as a person ages (Paillard et al, 2013). However, as there are a limited number of studies including older samples, these results should be interpreted with caution.…”
Section: Age and Vr Sicknesssupporting
confidence: 65%
“…Previous research has found inconsistent findings when looking at older samples (Benoit et al, 2015;Kennedy et al, 2010). Even though age has been reported as a user characteristic likely to predict motion sickness (Golding, 2006), the results from this review support previous research that there may be a decline in susceptibility to VR sickness as a person ages (Paillard et al, 2013). However, as there are a limited number of studies including older samples, these results should be interpreted with caution.…”
Section: Age and Vr Sicknesssupporting
confidence: 59%
“…Heightened anxiety in females may render them more susceptible to motion sickness than males, as heightened state- (Tucker and Reinhardt, 1967) and traitanxiety (Paillard et al, 2013) are strongly related to cybersickness (Ling et al, 2011).…”
Section: Female Hormonal Cyclementioning
confidence: 99%